Rola Tadeusza Banachiewicza w działalności Polskiej Akademii Umiejętności na przykładzie Komitetów Narodowych - Skrzyński, Tomasz (Przegląd Nauk Historycznych, 2012)
Before Word War I Conseil Internationalde Recherches was the most important interational organisation as far as sciences were concerned. A row of international unions were attached to it. Since 1921 PAU (Polish Academy of Sciences) was country’ s official representative at international science unions. Several national committees were the Academy’s auxiliary bodies for the Union matters. Top representatives of particular branches of science belonged to these. Tomasz Banachiewicz, an astronomer, mathematician and geophysicist was the chairman of most delegations sent by the Corporation for congresses of Survey – Geophysical Union and International Astronomy Union. He was also the chairman and played important role at domestic and international activities of National Commitees: Survey – Geophysical and Astronomy.